Evaluation of one-point fixation for zygomaticomaxillary complex fractures using a three-dimensional photogrammetric analysis - Kim, Se Young (J Otolaryngol Head Neck Surg, 2019)
BACKGROUND: The goal of treatment for zygomaticomaxillary (ZM) complex (ZMC) fractures is to achieve stability and restore aesthetic appearance through three-dimensional reduction and rigid fixation. The purpose of this study was to evaluate the stability and aesthetic appearance outcomes of one-point fixation using a three-dimensional photogrammetric analysis. METHODS: From March 2014 to December 2014, 34 patients with ZMC fractures were treated by one-point fixation in the ZM buttress using unsintered hydroxyapatite (u-HA)/poly-L-lactide (PLLA) plates. Differences in soft tissue inter-malar height between the fractured side and unfractured sides were evaluated using photogrammetric analysis with a three-dimensional camera (Morphius®) at the preoperative and 1 week, 1 and 3 months after surgery. The differences in bony inter-malar height between the fractured and unfractured sides were evaluated using computer tomography at the pre-operative and 6 months after surgery. The paired t-test was used to compare differences in malar height. RESULTS: Six months after surgery, 34 patients achieved satisfactory bony stability and symmetric malar appearances. Comparisons of differences in soft-tissue inter-malar height revealed statistically significant differences between the pre-operative period and 1 week and 1 month after surgery (p < .01). There was no statistically significant difference between 1 and 3 months after surgery. Comparison of differences in bony inter-malar height revealed a statistically significant difference between before and 6 months after surgery (p < .01). CONCLUSIONS: When we conducted a three-dimensional photogrammetric analysis, although it has restricted surgical indications, one-point fixation of the ZM buttress using an u-HA / PLLA plate yielded reliable, satisfactory, and safe clinical results in patients with ZMC fractures. CLINICAL QUESTION / LEVEL OF EVIDENCE: Therapeutic, III.